Development of In-Vitro Culture of Phalaenopsis Blackjack Orchid. - Nur Fazilah Musa (2019)
Phalaenopsis Blackjack orchid, originates from Taiwan has high demand due to its popularity as cut flowers and potted plants. However due to its low seed formation and low conventional breeding, the demand for Phalaenopsis Blackjack could not be fulfilled, hence this study was done. Aseptic technique to develop in-vitro culture of Phalaenopsis Blackjack was carried out by using leave as explant. There were three surface sterilization used to investigate the effect of different surface sterilization technique towards in-vitro culture of Phalaenopsis Blackjack orchid which was method A (sonication), method B (shaker) and method C (shaker and activated charcoal in media). Apart from that, to investigate the effect of hormone combinations toward Phalaenopsis Blackjack orchid multiplication, different hormone combinations with different concentrations Naphthaleneacetic acid (NAA; 0, 0.1, 1 mg/l) and Thidiazuron (TDZ; 0, 1, 3 mg/l) were used. In this experiment, survival rate, contamination rate and appearance were analysed and observed. Sonication method was found to be the most effective surface sterilization method compared by using shaker while 1⁄2 MS media supplemented with 0.1 mg/l NAA and 1 mg/l TDZ was the best treatment in multiplication of Phalaenopsis Blackjack orchid.